(untitled) (LEARNing Landscapes, 2012)
Graduates often find conceptualizing and writing long research projects an arduous alienating process. This paper1 describes a research writing intervention conducted at Memorial University in Newfoundland with two groups of graduate students (Engineering and Arts). One small part of the workshop was devoted to creative "sentence activities." Our argument is that these creative activities contributed to re-connecting students to themselves as researchers/writers and to others in the group. The activities engaged students in language literally, metaphorically, and performatively.